Plant form and height across environmental gradients: a developmental perspective on plant intraspecific variability - Chiminazzo, Marco A [UNESP]; Charles-Dominique, Tristan; Fidelis, Alessandra [UNESP]; Bombo, Aline B [UNESP]; Jones, Cynthia S; Diggle, Pamela K (Oxford University Press (OUP), 2025)
BACKGROUND AND AIMS: Many species have both tree and shrub growth-forms and, for some, the capacity to shift between single and multi-stemmed growth can be linked to changing environmental conditions. Such growth form variability can result from different developmental trajectories of perennial shoots located above- and/or belowground. Some of these responses are initiated at early life stages and propagate throughout ontogeny. This implies that conditions experienced during early life stages can impose legacy effects at later stages, defining whole plant ontogenetic trajectories and impacting form. Here we explore how environmental factors experienced at different stages of ontogeny can influence forms. METHODS: We focus on a generalist species (Handroanthus ochraceus, Bignoniaceae) growing in a range of fire-disturbance and light availability conditions across tropical forests and savannas. KEY RESULTS: Depending on the presence of a disturbance regime experienced early in ontogeny, individuals may develop either as multi- or single-stemmed plants. Importantly, growth form variability can be induced early in development, likely translating into growth form plasticity. CONCLUSIONS: We discuss the possible generalization of our observations to other taxa and whether variation in plant form is due to genetic differentiation or plasticity. Finally, we call for more studies of woody plant plasticity and how plasticity can be modulated through ontogeny.